2016
DOI: 10.9734/ajee/2016/30635
|View full text |Cite
|
Sign up to set email alerts
|

Height-diameter Relationship Models for Teak (Tectona grandis) Plantation in Nimbia Forest Reserve, Nigeria

Abstract: The study on height-diameter modelling was carried out on Teak (Tectona grandis) plantation in Nimbia Forest Reserve. Two fit methods (Chapman-Richards and Weibull) were used to model height-diameter relationship. The teak plantation is divided into four forest beats as management unit, therefore, stratified random sampling was employed to select five plots of 20 x 20 m from each forest beat (as stratum), thereby having a total of 20 plots. Stump diameter (Dst), diameter at breast height (Dbh), diameter at mid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 10 publications
(13 reference statements)
0
8
1
Order By: Relevance
“…Results obtained on DBH also shows that the 14 years (2009) age series had the highest mean DBH of 0.56 m, followed by the 13 years (2010) and 12 years (2011) with 0.53 m each, while the 11 years (2012) old age series had the least (0.42 m). The mean diameter in all the age series is lower than what was obtained in the University of Ibadan teak plantation (Adesoye and Oluwadare 2008), teak stands in Osho Forest Reserve (Popoola and Adesoye 2012) and teak plantation in Nimba forest reserve (Shamaki et al 2011). The results on average basal area across age series revealed that the 14 years (2009) age series had 0.26 m 2 which is the highest, followed by 13 years (2010) and 12 years (2011) both having 0.24 m 2 , while the while 11 years (2012) old age series had the least (0.14 m 2 ).…”
Section: Tree Growth Variables In the Different Age Series In The Stu...contrasting
confidence: 63%
“…Results obtained on DBH also shows that the 14 years (2009) age series had the highest mean DBH of 0.56 m, followed by the 13 years (2010) and 12 years (2011) with 0.53 m each, while the 11 years (2012) old age series had the least (0.42 m). The mean diameter in all the age series is lower than what was obtained in the University of Ibadan teak plantation (Adesoye and Oluwadare 2008), teak stands in Osho Forest Reserve (Popoola and Adesoye 2012) and teak plantation in Nimba forest reserve (Shamaki et al 2011). The results on average basal area across age series revealed that the 14 years (2009) age series had 0.26 m 2 which is the highest, followed by 13 years (2010) and 12 years (2011) both having 0.24 m 2 , while the while 11 years (2012) old age series had the least (0.14 m 2 ).…”
Section: Tree Growth Variables In the Different Age Series In The Stu...contrasting
confidence: 63%
“…Figure 2 indicates that the increase in height is linearly followed by the increase in diameter. The linear relationship between tree height and diameter was also occurred on Chamaecyparis obtusa (Sumida et al 2013) and also on teak stand in Nigeria (Shamaki et al 2016).…”
Section: Discussionmentioning
confidence: 75%
“…While Naslund had RMSE of 2.29 and 2.81, respectively, for the two species in their study. Also, Shamaki et al [40] reported R 2 and RMSE of 0.336 and 0.995 and 0.335 and 0.995 for Chapman-Richards and Weibull H-D models, respectively, for Tectona grandis in Nimbia Forest Reserve. There is no basis for comparing the fit indices values of the study at hand and others reported in forestry literatures.…”
Section: Resultsmentioning
confidence: 97%